An overview on Photobiomodulation in Temporomandibular Joint Dysfunction (Journal of Pharmaceutical Negative Results, 2022)
Photobiomodulation , also known as low-level laser therapy, is the application of red and near-infrared light to promote healing, pain relief, and inflammation reduction. This brief review focuses on the detailed physiology of how this device works and its use in temporomandibular joint dysfunction. Photobiomodulation acts at the cellular level, stimulating the mitochondrial respiratory chain in cytochrome c oxidase and increasing ATP and mitochondrial membrane potential, allowing cells to regenerate and repair themselves. By acting on inflammatory mediators, it promotes tissue healing and reduces inflammation. This anti-inflammatory and healing property can be used to treat a variety of skin, joint, and soft tissue conditions. Photobiomodulation has also been shown to provide significant pain relief when compared to other treatment options. This therapy employs the use of light emitting diodes. In studies focusing on its use in the temporomandibular joint, it has been shown to be effective in reducing pain in joint-related conditions such as degenerative arthritis or myopathic pain by promoting metabolic action.